Comparative parallel multi-omics analysis during the induction of pluripotent and trophectoderm states - Mohammad Jaber; Ahmed Radwan; Netanel Loyfer; Mufeed Abdeen; Shulamit Sebban; Areej Khatib; Hazar Yassen; Thorsten Kolb; Marc Zapatka; Kirill Makedonski; Aurelie Ernst; Tommy Kaplan; et al. (Nature Communications, 2022)
Ectopic transcription factor expression can reprogram mouse fibroblasts to pluripotent or trophoblast stem cells. Here the authors apply multi-omics analyses to the induction of pluripotency and trophoblast stem cell state from fibroblasts, comparing these with the changes in transcriptome of early embryonic cells.